PENGGUNAAN VIDEO PEMBELAJARAN DENGAN BANTUAN GEOGEBRA DAN PEN TABLET PADA MATA KULIAH GEOMETRI ANALITIK RUANG - Ramadhani, Widya Putri; Silitonga, R H Yanti (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
Learning Videos are one of the effective learning media in supporting the teaching and learning process during the COVID-19 Pandemic. With the help of the geogebra application and pen tablet tools made in the form of learning videos, it is very helpful for students to understand abstract concepts to be visually clear. (This research is a study with a pretestt-postestt non equivalent control group design. The experimental class was treated with a learning video made with the help of the geogebra application and pen tablet while the control class learned using powerpoint. The results obtained by the value of Sign. (2-tailed) testing of the N-Gain score is 0.00 less than a so that H0 is rejected, meaning that the improvement in the learning outcomes of experimental class students is better than control class students, meaning that there is a difference in the improvement of student learning outcomes on spherical material in the analytical geometry course of significant space